2012
DOI: 10.1016/j.meatsci.2011.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Carnosic acid dietary supplementation at 0.12% rates slows down meat discoloration in gluteus medius of fattening lambs

Abstract: Thirty-two Merino lambs fed barley straw and a concentrate alone (CONTROL) or enriched with vitamin E (VITE006) or carnosic acid (CARN006; CARN012) were used to assess the effect of these antioxidant compounds on meat quality attributes. The animals were slaughtered after being fed for at least 5weeks with the experimental diets. The longissimus lumborum samples of VITE006, CARN006 and CARN012 groups showed higher values (P<0.001) of L* (lightness) through the complete storage period under modified atmosphere … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 23 publications
3
40
3
Order By: Relevance
“…In relation to drip loss, in the study of Morán et al (2012b), no significant differences were observed in water-holding capacity between control and groups supplemented with CA and vitamin E. Also, Skřivanová et al (2007) and Vignola et al (2009) demonstrated no effect of Se on natural drip loss in meat. In turn, Li et al (2011) showed that increased levels of SeY decreased the drip loss in the muscle.…”
Section: Effect Of Lamb Diets On Meat Quality Characteristicsmentioning
confidence: 89%
See 4 more Smart Citations
“…In relation to drip loss, in the study of Morán et al (2012b), no significant differences were observed in water-holding capacity between control and groups supplemented with CA and vitamin E. Also, Skřivanová et al (2007) and Vignola et al (2009) demonstrated no effect of Se on natural drip loss in meat. In turn, Li et al (2011) showed that increased levels of SeY decreased the drip loss in the muscle.…”
Section: Effect Of Lamb Diets On Meat Quality Characteristicsmentioning
confidence: 89%
“…Nevertheless, pH 48 values recorded in groups fed with CA and SE (groups III, IV, and V) were intermediate between group RO (group I) and FO (group II). A study by Morán et al (2012b) showed significant and lower pH 24 in meat of lambs fed CA (0.6 g kg −1 ) compared to the control group, and no respective differences in the group with CA dose of 1.2 g kg −1 . No significant differences between ultimate pH of lambs fed CA in comparison to the control group were found in studies by Bañón et al (2012) and Ortuño et al (2014).…”
Section: Effect Of Lamb Diets On Meat Quality Characteristicsmentioning
confidence: 93%
See 3 more Smart Citations